Quality of life among adolescents with substance use disorders - Khan, Rubaiya; Ahsan, Mohammad Shamsul; Shah, Md. Tanvir Rahman; Dutta, Bijoy Kumar; Nath, Mukul Chndra (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Adolescents are vulnerable to substance use, which profoundly affects their function, feelings and quality of life (QoL). This study aimed to assess the physical health, psychological, social relationships, and environmental domains of QoL among adolescents with substance use disorders (SUDs). Methods: A cross-sectional study was done from October 2020 to September 2021 among 44 adolescents selected purposively from Central Drug Addiction Treatment Center (CDC), Dhaka and Ashokti Punorbashon Nibash (APON), Manikganj. Clinical diagnosis was assigned using The Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) by psychiatrists. Then, they were interviewed with a questionnaire and a Bengali Version of the World Health Organization quality of life scale brief version (WHOQOL-BREF). Results: Among the 44 adolescents with SUD, 18 (40.9%) rated their QoL as poor, 14 (31.8%) as very poor, 8 (18.2%) as neither poor nor good, and only 4 (9.1%) as good. Nearly half of them (47.7%) reported that they were dissatisfied, one third (29.5%) were very dissatisfied with their health. Among the four domains, the psychological domain (9.8±2.3) had the lowest mean score, followed by physical health (10.5±2.7), social relationships (10.6±2.6), and environmental domain (11.5±2.2) of the WHOQOL-BREF. Multiple drug users had poorer scores of their QoL than single drug user. Conclusion: Our study demonstrated that all domains of QoL (physical, psychological, social, and environmental) are impaired in adolescents with SUDs.